Shane Leslie and the Irish Support for Language Struggle in Poland - Gmerek, Katarzyna (Studia Celtica Posnaniensia, 2018)
This paper tells a little known story of the collecting and delivery of signatures of Irish school children from the northern part of Ireland as an act of moral support for Polish students on strike in defense of the Polish language at schools in the Prussian partition of Poland, in the first decade of the 20th century (Płygawko 1991). The bound signatures are in the Czartoryski Museum in Cracow, Poland, but the information about the action has not been found in Irish sources, and the Polish signatures collected in response seem to be missing. The role of the organizer of the initiative, Shane Leslie, is emphasized in this paper. It describes the background of this exchange of sympathy, and discusses possible reasons why the story remains obscure.